2017
DOI: 10.1515/tnsci-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

White matter sexual dimorphism of the adult human brain

Abstract: Sex-biased psychophysiology, behavior, brain function, and conditions are extensive, yet underlying structural brain mechanisms remain unclear. There is contradicting evidence regarding sexual dimorphism when it comes to brain structure, and there is still no consensus on whether or not there exists such a dimorphism for brain white matter. Therefore, we conducted a voxel-based morphometry (VBM) analysis along with global volume analysis for white matter across sex. We analyzed 384 T1-weighted MRI brain images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Although in the human literature there exist no consensus as to the presence of a sexual dimorphism in either the brain's structure or white matter development, 30,87 in the subset of studies that include both male and female subjects, we see a clear sex difference. From this, it is critical that future studies include both male and female subjects in their design.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Although in the human literature there exist no consensus as to the presence of a sexual dimorphism in either the brain's structure or white matter development, 30,87 in the subset of studies that include both male and female subjects, we see a clear sex difference. From this, it is critical that future studies include both male and female subjects in their design.…”
Section: Discussionmentioning
confidence: 68%
“…Conversely, a separate study found evidence that females have regionspecific elevations in myelin in the corpus callosum in the genu vs splenium vs main body 86. Females display increased volume in the hippocampus, locus coeruleus, Broca's area and Wernicke's areas when compared to their male counterparts 33,87,88. In humans, these sex specific asymmetries are found in multiple brain regions16,40,89 that are not reflected in global white matter assessments87 and not due to a sexspecific difference in overall brain volume 88.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These masks were employed to quantify ROI volume and connectivity as in [54,55]. The whole brain, intracranial, and ROIs volume were determined with the get_totals script (cs.ucl.ac.uk), such as in [57,58]. This script takes one segmented MRI set, i.e., all the images for a given brain tissue, as input and then returns its volume expressed in mm 3 .…”
Section: Brain Volume Calculation and Mask Constructionmentioning
confidence: 99%